Application of Talking Stick Co-operative Model to Improve Students' Mathematics Learning Activity and Result in Primary School - Fatimah, Iim; Suhada, Dadang; Khoimatun, Khoimatun (Transpublika Publisher, 2025)
The objective of this research is to increase the engagement and academic achievement of fourth-grade students at SDN 2 Benda Karangampel, Indramayu in mathematics by implementing the Talking Stick cooperative learning approach. After consulting with teachers, it was identified that the inadequate utilization of educational resources and the limited diversity in teaching techniques are contributing factors to the students' poor performance. Consequently, this has resulted in a lack of student participation during lessons, as evidenced by only 9% of students achieving a score above the passing mark (65) in the Mid-Semester Assessment (PTS). This research project involves Classroom Action Research (PTK), conducted over three phases: planning, execution, observation, and reflection. The findings indicate that the introduction of the Talking Stick method enhanced the efficiency of the learning process. Evaluations of the teaching process improved from 71% (good category) in the first cycle to 86% (very good category) in the third cycle. Student engagement levels also rose from 61% (active category) in the initial cycle to 83% (very active category) in the final cycle. Moreover, student achievements increased from 54% (19 pupils) in the beginning to 86% (30 pupils) by the end, surpassing the 80% threshold for success. Consequently, the application of the Talking Stick cooperative learning model has been shown to be effective in boosting student participation and results in mathematics education. This innovative approach could offer a unique and enjoyable educational experience for students.